A Survey on EFL Students’ Readiness to Use ChatGPT in English Learning at One of the publics Senior High Schools in North Bali - Ni Komang Anggi Tri Jayanti; Made Hery Santosa; Luh Indrayani (The Future of Education Journal, 2026)
This study was conducted to examine the readiness of EFL students across different grade levels to utilize ChatGPT as a supportive tool in English language learning, based on the RAIS framework, in response to the lack of empirical investigation into students’ preparedness in terms of technology self-efficacy, student interaction, and ethical awareness as a foundation for effective and responsible AI integration in secondary education. This study aimed to investigate the readiness of EFL students to use ChatGPT in English learning at one of the publics Senior High Schools in North Bali. This research employed a quantitative survey method, in which data were collected using a questionnaire and analyzed using statistical techniques. The population of this study consisted of EFL students at One of the publics Senior High Schools in North Bali, with samples drawn from students in grades 10, 11, and 12. The results of the study revealed that (1) The overall level of readiness of EFL students at One of the publics Senior High Schools in North Bali to use ChatGPT in English learning was high. These findings indicate that students are capable of accessing and utilizing artificial intelligence-based technology and possess adequate attitudes, self-confidence, and ethical awareness to integrate ChatGPT into their English learning process. (2) Differences in readiness levels among EFL students in grades 10, 11, and 12 at One of the publics Senior High Schools in North Bali showed no statistically significant differences. This finding indicates that readiness to use ChatGPT as a supporting tool for English learning is relatively uniform across grade levels, suggesting that contextual and pedagogical factors, such as consistent curriculum, institutional support, and exposure to technology-integrated learning, play a more critical role than grade level or academic progression in shaping students’ technology readiness. Future researchers are recommended to expand the scope of the study by involving multiple institutions, employing mixed-method approaches, and examining the relationship between students’ AI readiness and actual English learning outcomes to provide a more comprehensive understanding of effective ChatGPT integration in secondary education.